Four cases of omental herniation in cattle. Issue 1 (11th July 2013) - Pardon, B.; Vertenten, G.; Durie, I.; Declercq, J.; Everaert, D.; Simoens, P.; Deprez, P.
Abstract : Four cases in cattle of omental herniation through an acquired omental rent are described. Clinical signs were indistinguishable from other causes of mechanical ileus and exploratory laparotomy was necessary to establish a diagnosis. In all cases a variably sized portion of jejunal loops was obstructed in an omental rent in the deep layer of the greater omentum. In two cases simple reduction was possible, and in one case incision of the hernial ring was necessary before reduction could be performed. Resection was necessary only in a calf, in which the incarceration was complicated by severe abomasal distension and local peritonitis. In all four cases the omental rent was closed by a serosa‐serosa suture. Three cases made an uneventful recovery and returned to normal production, but one of these animals died three months postoperatively from an unknown cause. The calf was euthanased two days postoperatively because of persistent ileus.